Soul Dimension and Antithesis of Ibnu Sina’s Reincarnation Concept - Naila Shofia; Achmad Khudori Soleh (IAIN Pekalongan, 2022)
Ibn Sina, the father of modern medicine, has an unusual concept of psychology. His concept of soul is different from other characters. So is his view of reincarnation. This study examines Ibn Sina's concept of the soul and his views on reincarnation. The research is based on literature data and uses qualitative methods. The results showed that Ibn Sina divided the human soul into three parts: the plant, animal, and human. The human soul is eternal. The soul is not corrupted after death, after being separated from the body. The soul lives on in its nature. After death, the soul does not need a new body for its activities. Therefore, there is no reincarnation for the soul. Ibn Sina disagrees with the concept of soul reincarnation by Aristotle.